Analysis of diagram errors in selected Nigerian secondary school practical biology textbooks - Bello Ganiyu; Olajuwon Michael Aransiola; Aromire Fuad; Alani Christiana (Universitas Ahmad Dahlan, 2021)
Evidence abounds in science education literature that science textbooks are not alwayserror-free and that inaccuracy in diagrams creates confusion, misconceptions, and hinders meaningful learning. Therefore, in this textbook research study, an attempt was made to identify, analyse, and classify diagram errors in four selected Nigerian biology practical textbooks. The purposive sampling technique was used to select four widely used practical biology textbooks. Two instruments designed by the researchers namely, Compendium of Practical Biology Textbooks (CPBT) and Diagram Error Identification Proforma (DEIP) were used for data collection. Each diagram in the four selected textbooks was carefully analyzed for the identification of errors. The identified errors were analysed, classified, coded, and subjected to statistical analysis. Results indicated that diagrams in the four textbooks were rife with spelling, labeling, and technical errors and that there was a significant difference between the numbers of diagram errors in the four selected textbooks in favor of Textbook C. It was concluded that the selected Nigerian practical biology textbooks were laden with various types of diagram errors that could impact students performance negatively. Urgent revision of the textbooks was recommended to stem the negative impacts of the diagram errors on students performance.